Plant growth–promoting traits of culturable seed microbiome of citrus species from Purvanchal Himalaya - Sinha, Sakshi; Thakuria, Dwipendra; Chaliha, Chayanika; Uzir, Panchali; Hazarika, Samarendra; Dutta, Pranab; Singh, A. K.; Laloo, Bingiala (Frontiers in Plant Science, 2023)
Despite Northeastern India being "Treasure House of Citrus Genetic Wealth", genetic erosion of citrus diversity poses a severe concern with a corresponding loss in seed microbial diversity. The seed microbiome of citrus species unique to the Purvanchal Himalaya is seldom explored for their use in sustainable orchard management. Isolation and characterisation of culturable seed microbiomes of 8 citrus species namely Citrus reticulata Blanco, Citrus grandis (L.) Osbeck, Citrus latipes Tanaka, Citrus megaloxycarpa Lushaigton, Citrus jambhiri Lush, Citrus sinensis (L.) Osbeck, Citrus macroptera Montr, and Citrus indica Tanaka collected from NE India were carried out. The isolates than were screened for an array of plant growth promoting (PGP) traits (IAA production, N2 fixation, Phosphate and Zinc complexes dissolution, Siderophores and HCN production). The pure culture isolates of seed microbiomes were capable of dissolving insoluble Ca3(PO4)2 (1.31 - 4.84 µg Pi ml-1 h-1), Zn3(PO4)2 (2.44 - 3.16 µg Pi ml-1 h-1), AlPO4 (1.74 - 3.61 µg Pi ml-1 h-1), and FePO4 (1.54 - 4.61µg Pi ml-1 h-1), mineralized phytate (12.17 - 18.00 µg Pi ml-1 h-1) and produced IAA-like substances (4.8 - 187.29 µg ml-1 h-1). A few isolates of seed microbiome were also able to fix nitrogen, secrete siderophores-like compounds and HCN, and dissolve ZnSO4 and ZnO. The 16S rRNA based taxonomic findings revealed that Bacillus was the most dominant genus among the isolates across citrus species. Isolates CG2-1, CME6-1, CME6-4, CME6-5, CME6-9, CJ7-1, CMA10-1, CI11-3, and CI11-4 were identified as promising bioinoculants for development of microbial consortium having multifaceted PGP traits for nutritional benefits of nitrogen, phosphorus and zinc, and IAA hormonal benefits to citrus crops for better fitness in acid soils.